Assessment and analysis the performance of Multi-Hop Internet of Underwater Things Networks - Khider, Ibrahim; Raied Ibrahim (University of Khartoum Engineering Journal, 2025)
Internet of Underwater Things (IoUT) is one of the technologies that building smart cities , but it must overcome several challenges including environmental concerns ,connectivity barriers and system architecture complexities.This paper presents a performance analysis of Multi-Hop Internet of Underwater of Things Networks.we examine and assess the performance of multi hop IoUT networks in term of several key metrics ,including throughput, network efficiency, packet loss rate, and signal-to-noise ratio (SNR).The analysis provides valuable insight on the performance of multi hop IoUT networks, highlighting their performance and limitations. Keywords IoUT,Multi-Hop networks,underwater communication